2011
DOI: 10.24926/iip.v2i2.223
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Continuing Professional Development program for first year student pharmacists undergoing an Introductory Pharmacy Practice Experience

Abstract: Objectives: The purpose of the study was to evaluate a live and online training program for first year pharmacy students in implementing Continuing Professional Development (CPD) principles (Reflect, Plan, Act, and Evaluate), writing SMART learning objectives, and documenting learning activities prior to and during a hospital introductory professional practice experience. Design: Cohort Study. Setting: Introductory professional practice experience. Participants: First year (PY1) students at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…5 The CPD cycle used in this study was adapted with permission from the Ontario College of Pharmacists and follows the same approach. 6,7 Positive results have been reported with pharmacists trained in the CPD approach. In a 10-month study of licensed pharmacists employed at a health maintenance organization (HMO), a higher percentage of those randomized to CPD vs. CE reported that they had better interactions with other healthcare providers and initiated practice changes as a result of their educational activities.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…5 The CPD cycle used in this study was adapted with permission from the Ontario College of Pharmacists and follows the same approach. 6,7 Positive results have been reported with pharmacists trained in the CPD approach. In a 10-month study of licensed pharmacists employed at a health maintenance organization (HMO), a higher percentage of those randomized to CPD vs. CE reported that they had better interactions with other healthcare providers and initiated practice changes as a result of their educational activities.…”
Section: Introductionmentioning
confidence: 81%
“…Additional details have been previously described. 7 While the live CPD training module has been effective for pharmacists, it was offered to students on a voluntary basis because of the challenge of training more than 100 students in a short timeframe prior to the start of summer practice experiences. 6 CPD Webcasts on the ACPE Web site were available to students who opted not to participate in live training.…”
Section: Year 1 Of Implementationmentioning
confidence: 99%
See 3 more Smart Citations